“Inclusivity requires an active effort”: building an inclusive and diverse space when engaging people with lived and living experience and caregivers in mental health and substance use health research - Amartey, Abigail; Hauer, Shoshana; Munro, Charlotte; Sendanyoye, Claudia; Upham, Katie; van Kesteren, Mary R.; Halsall, Tanya; Lunsky, Yona; Hawke, Lisa D. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Engaging people with lived/living experience and caregivers (PLLEX-C) in mental health and substance use health research has many advantages for scientists, research staff, and PLLEX-C. However, research teams must be cognizant of the wide spectrum of human diversity. As such, engagement settings that are inclusive and reflect the diversity of the populations being served are essential to meaningful and impactful research. Objective The aim of this qualitative descriptive study was to understand the perspectives of PLLEX-C on how to build inclusive and diverse research spaces when engaging PLLEX-C in mental health and substance use health research. Methods We recruited 20 PLLEX-C with experience engaging in mental health and substance use health research to participate in one of five focus group discussions. The focus groups were audio recorded and transcribed, with codebook thematic analysis conducted using a deductive and inductive approach. This study team included a Lived and Living Experience and Caregiver Working Group throughout all phases of the research project. Results Four themes were identified across the five focus group discussions: 1) Acknowledge that diversity is inclusive of different factors and this needs to be reflected in the recruitment process to improve the research. 2) Remove barriers of entry into the research space. 3) Ensure that the scientists and staff are trained and skilled in inclusive and diverse engagement. 4) Build a safe and equitable engagement space. Within these themes, subthemes were also identified and described with illustrative quotes. Conclusions Identifying ways to ensure research engagement settings are inclusive and diverse for all those involved requires an intentional and active effort at all stages of the research process. This includes not only employing various recruitment strategies to identify more diverse PLLEX-C, but also continuous, ongoing training for researchers to ensure engagement is culturally sensitive, anti-discriminatory, and bias-free. Prioritizing research teams that are inclusive and diverse can foster an engagement experience that is more meaningful, authentic, and empowering.

Plain English summary In mental health and substance use health research, we see many benefits when people with mental health and/or substance use health experiences and challenges are included on research teams. They are referred to as ‘people with lived/living experience and caregivers’ (PLLEX-C). We wanted to understand how to create a more inclusive, diverse space for the people engaged in these roles. We held five group discussions with PLLEX-C who have previously been members of mental health and substance use health research teams. They were asked to share their thoughts on how research teams can include PLLEX-C from more diverse backgrounds. Participants said that diversity is made up of different characteristics that should be included on teams; that research spaces need to be free of barriers that prevent individuals from taking part in the research; that scientists and research staff must receive diversity and inclusion training; and that the research space must make everyone feel safe and equal to others. Mental health and substance use health research teams need to make an active effort to include PLLEX-C from more diverse backgrounds as people’s health and their care experiences will vary across socioeconomic factors, ethnicity, gender, age, and other identity factors. This will lead to more people being included in the research process, and will lead to higher quality research.